Enhancement of ZnO nanostructures Properties Grown by Electrochemical deposition technique - Shahad A.D.; N.K. Hassan; Q.H. Mahmood (Tikrit Journal of Pure Science)
ZnO nanostructure has been successfully synthesized on n-type Si (111) by electrochemical deposition method. The (FESEM) Images Showed that the Seed-shaped ZnO nanostructures with 20 nm radius occurred by changing the annealing time. The x-ray diffraction (XRD) revealed that ZnO were hexagonal grown with very high (101) orientation. The Optical gap spectrum proves that the grown ZnO Seed-shaped nanostructures of a very high quality in the UV region from electromagnetic spectrum.